2021
DOI: 10.7759/cureus.16503
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation: A Microbiome Modulation Technique for Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia and the fifth leading cause of death among the elderly. AD involves parts of the brain that can lead to progressive memory loss and impaired language skills and cognitive thinking, affecting one's ability to carry out daily activities. Aging, bad dietary habits, family history, as well as altered gut microbiota composition may play a role in the pathogenesis of AD. Although the association between the imbalance of gut microbiota and AD is still diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…2 ). FMT is currently used for Clostridium difficile infection relapses [ 102 ], but potentially could be therapeutic for a variety of conditions where the GMB has been linked to pathological progression [ 103 , 104 ]. In AD, a pair of studies were published recently demonstrating the effectiveness of FMT in reducing pathology in AD mouse models [ 105 , 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). FMT is currently used for Clostridium difficile infection relapses [ 102 ], but potentially could be therapeutic for a variety of conditions where the GMB has been linked to pathological progression [ 103 , 104 ]. In AD, a pair of studies were published recently demonstrating the effectiveness of FMT in reducing pathology in AD mouse models [ 105 , 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…The realization that gut microbiota plays a role in maintaining homeostasis and regulating practically every major bodily system, including the central nervous system (CNS), has sparked a revolt in biomedicine during the last two decades [ 6 ]. The “gut–brain axis” (GBA) implies the existence of a two-way communication route between gut microorganisms and the CNS, is now widely accepted [ 7 ], and dysregulation of this axis is increasingly suspected of being involved in the pathophysiology of neurological disorders, such as Autism Spectrum Disorder, Alzheimer’s disease, multiple sclerosis, Parkinson’s disease, etc. [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both amyloid beta-peptide deposition [ 54 ] and mitochondrial damage [ 55 ] contribute to the development of Alzheimer’s disease (AD). With the deepening of the understanding of the gut microbiome, numerous studies have attempted to explain the underlying mechanism of AD from the perspective of gut microbiota [ 56 , 57 ], and to improve cognitive status through probiotics [ 58 ] or FMT [ 59 ]. Studies have found that microbial metabolites, such as trimethylamine N-oxide (TMAO) [ 60 ], lipopolysaccharide (LPS), and SCFAs [ 61 ], are associated with amyloid β-protein (Aβ) deposition in the brain.…”
Section: The Roles Of Ipa In Host Diseases and Healthmentioning
confidence: 99%